Kajian Semiotika Sumping Sekar Kluwih Wayang Kulit Purwa - Sugeng Nugroho (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2008)
This article talks about the aesthetic and symbolic meaning of sumping sekar kluwih in Surakarta purwa shadow puppet eith hermeneutic approach and semiotic analysis. Based on the aesthetic study, the decision of sumping model depends on space aspect and proportion with other accessories which are accessories which are close and/or related to it covering : sanggul, irah-irahan and praba. According to symbolic study sumping sekar kluwih is used by the character in shadow puppet that have character, attitude,cleverness,supernatural power,behavior, and/or live journey which is : (1) more than character positively (Java: Luwih ing sapepadha);(2) unusual(java: linuwih); and (3) unnatural or excessive (java : Kliwat).Keyword : sekar kluwih, sumping of purwa shadow puppet, semiotics.